Biometry and Intraocular Lens Power Calculation in Eyes with Prior Laser Vision Correction (LVC) – A Review - Wendelstein, Jascha; Heath, Michael; Riaz, Kamran M.; Seiler, Theo; Cooke, David L.; Langenbucher, Achim; Hoffmann, Peter; Kohnen, Thomas (Klinische Monatsblätter für Augenheilkunde, 2022)
Background An intraocular lens (IOL) calculation in eyes that have undergone laser vision correction (LVC) poses a significant clinical issue in regards to both patient expectation and accuracy. This review aims to describe the pitfalls of IOL power calculation after LVC and give an overview of the current methods of IOL power calculation after LVC.Review Problems after LVC derive from the measurement of anterior corneal radii, central corneal thickness, asphericity, and the predicted effective lens position. A central issue is that most conventional 3rd generation formulas estimate lens position amongst other parameters on keratometry, which is altered in post-LVC eyes.Conclusion An IOL power calculation results in eyes with prior LVC that are notably impaired in eyes without prior surgery. Effective corneal power including anterior corneal curvature, posterior corneal curvature, CCT (central corneal thickness), and asphericity is essential. Total keratometry in combination with the Barrett True-K, EVO (emmetropia verifiying optical formula), or Haigis formula is relatively uncomplicated and seems to provide good results, as does the Barrett True-K formula with anterior K values. The ASCRS ( American Society of Cataract and Refractive Surgery) calculator combines results of various formulae and averages results, which allows a direct comparison between the different methods. Tomography-based raytracing and the Kane and the Castrop formulae need to be evaluated by future studies.
Keywords: cataract; biometry; laser vision correction; intraocular lens; IOL formula